2012
DOI: 10.1080/08832323.2011.582897
|View full text |Cite
|
Sign up to set email alerts
|

Is Higher Better? Determinants and Comparisons of Performance on the Major Field Test in Business

Abstract: Student performance on the Major Field Achievement Test in Business is an important benchmark for college of business programs. The authors' results indicate that such benchmarking can only be meaningful if certain student characteristics are taken into account. The differences in achievement between cohorts are explored in detail by separating the effect of high-achieving students choosing certain majors (characteristics effect) from the effect of the returns on these characteristics that students realize dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…The MFT-B has attracted the attention of researchers seeking to identify the determinants of student performance on this widely used assessment. Standardized test scores (ACT/SAT), grade point average (GPA), majors field of study, and gender have been consistently cited as determinative covariates (Bielinska-Kwapisz, Brown, & Semenik, 2012a, 2012bBlack & Duhon, 2003;Bycio & Allen, 2007). This study extends the research stream by further and specifically examining the size and heretofore, unexamined nature of reported MFT-B performance differentials attributed to gender.…”
mentioning
confidence: 63%
See 2 more Smart Citations
“…The MFT-B has attracted the attention of researchers seeking to identify the determinants of student performance on this widely used assessment. Standardized test scores (ACT/SAT), grade point average (GPA), majors field of study, and gender have been consistently cited as determinative covariates (Bielinska-Kwapisz, Brown, & Semenik, 2012a, 2012bBlack & Duhon, 2003;Bycio & Allen, 2007). This study extends the research stream by further and specifically examining the size and heretofore, unexamined nature of reported MFT-B performance differentials attributed to gender.…”
mentioning
confidence: 63%
“…Gender, specifically male advantage, has been reported in several studies of performance on the MFT-B. Bielinska-Kwapisz et al (2012a) reported that men perform better than women by 4.33 points after controlling for ACT scores, GPA, and an offer of extra credit for performance. Mason, Coleman, Steagall, Gallo, and Fabritius (2011) reported a 4.9point male advantage on the MFT-B while controlling for GPA, SAT, age, transfer, race, and major; while Bagamery, Lasik, and Nixon (2005) reported male scores on the MFT-B that were eight points higher than those from women when controlling for essentially the same stock of covariates.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…Bielinska-Kwapisz et al (2012) point out that such benchmarking can only be meaningful if certain student characteristics are taken into account. Allen and Bycio (1997) reported that MFT performance was significantly associated with students' undergraduate GPA.…”
Section: Rq2mentioning
confidence: 98%
“…Class attendance (ATTEN) is reported to have positive impact on students' academic performance (Devadoss and Foltz, 1996;Harb and El-Shaarawi, 2007 Students' TOEIC scores are positively associated to their academic performance (Wilson, et al 2004;Koys, 2010). Grade point average (GPA) was revealed as the strongest predictive factor of students' performance (Koys, 2010;Bielinska-Kwapisz, et al 2012). …”
Section: Research Hypothesismentioning
confidence: 99%